Claudius und Livia in Urium? Ein Statuenfund im Erzrevier von Riotinto (Prov. Huelva) - Pérez Macías, Juan Aurelio; Schattner, Thomas G.; Gimeno Pascual, Helena; Stylow, Armin Udo (Madrider Mitteilungen, 2020)
Zusammenfassung folgt.